2020
DOI: 10.1186/s12913-020-05700-w
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and socioeconomic inequalities in the utilization of maternal healthcare services in Nigeria: 2003–2017

Abstract: Background Maternal mortality has remained a challenge in many low-income countries, especially in Africa and in Nigeria in particular. This study examines the geographical and socioeconomic inequalities in maternal healthcare utilization in Nigeria over the period between 2003 and 2017. Methods The study used four rounds of Nigeria Demographic Health Surveys (DHS, 2003, 2008, 2013, and 2018) for women aged 15–49 years old. The rate ratios and differences (RR and RD) were used to measure differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 42 publications
6
46
0
1
Order By: Relevance
“…The country is divided into six geopolitical zones: North-Central, North-East, North-West, South-East, South-South, and South-West with each geopolitical zone comprising about six states [ 19 ]. Of the six zones, the northern geopolitical zones especially the North West and North East have the highest poverty rates in the country [ 20 ]. The health care system in Nigeria is largely public sector driven, with substantial private sector involvement in service provision.…”
Section: Methodsmentioning
confidence: 99%
“…The country is divided into six geopolitical zones: North-Central, North-East, North-West, South-East, South-South, and South-West with each geopolitical zone comprising about six states [ 19 ]. Of the six zones, the northern geopolitical zones especially the North West and North East have the highest poverty rates in the country [ 20 ]. The health care system in Nigeria is largely public sector driven, with substantial private sector involvement in service provision.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that various districts have more resources and health care infrastructure than others, or perhaps different regions have different sociocultural norms around gender equality and reproduction. Reports from previous studies showed regional differences in the uptake and utilization of health care services [ 47 51 ]. In addition, older women and those who were married had a reduction in the risk of first abortion.…”
Section: Discussionmentioning
confidence: 99%
“…The results could reflect the fact that better-off individuals might have better access to the antenatal clinic during pregnancy, where exclusive breastfeeding is a regular topic during health education sessions and is commonly a part of advocacy messages. These results have implications for SBC programming in northern Nigeria, where the poor are consistently disadvantaged in the population's access to healthcare [49,50].…”
Section: Discussionmentioning
confidence: 98%